Parental Social Support and Achievement Motivation on Self-Regulated Learning Strategy with an Interest as a Mediator Variable - Saputra, Dhanu; Daliman, Daliman (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2021)
Social cognitive theory explains how the individual's environment can influence the emergence of intrinsic motivation which can encourage students to be able to learn independently and be able to achieve learning goals. This study aims to analyze the effect of parental social support and achievement motivation with self-regulated learning with interest as a mediator variable. This research was conducted in 3 different schools. The number of the population in this study amounted to 730 students. While the number of samples used was 288 students. The sampling technique in this study used purposive sampling technique with the criteria for assessing favorite, ordinary and less favorite schools based on the assessment of the surrounding community. The data analysis technique used is the Structural Equation Modeling (SEM) model with the AMOS program. The results of this study indicate that there is a significant influence between social support and achievement motivation on interest. There is a significant influence between social support, achievement motivation and interest in self-regulated learning. There is an influence between social support and achievement motivation on self-regulated learning through interest variables. Students who have high motivation tend to apply high self-regulated learning so that students are encouraged to improve their performance, have the courage to take risks, are creative, and innovative. This can be used as a theoretical and empirical reference in developing student learning independence.